Coffee Experience as an Attraction for Indonesian Gen Z Tourists in Heritage Area of Braga - Adrian Agoes; Indah Nur Agustiani (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2023)
The Braga heritage area is among the most famous tourist destinations in Bandung, Indonesia as this street is the location of numerous colonial-style heritage structures. Meanwhile, Generations Z reportedly will predominate the majority of travelers in the travel and tourism industry. They are viewed, though, as lacking a strong enough fascination with the subject of quality tourism including historical and heritage attractions. Interestingly, the coffee experience, which is also increasingly available in Braga, is beginning to draw the interest of Generation Z. The research question is whether the growth of heritage tourism such as in Braga Street, which rely on historical narrative, will be supported in the future by the rise of the Gen-Z tourist market circles, and whether coffee experience will be strong enough to attract them to come. In this qualitative research approach, ten respondents were agreed to describe their experiences as they perceived them. This study finds that the attractiveness of heritage buildings in the Braga area and the coffee experience are mutually reinforcing. If there was no place for Generation Z to get coffee, they would be hesitant to visit the Braga Heritage area to admire the historic buildings. The heritage atmosphere provided in the Braga area, on the other hand, was reported to be what inspired Gen Z tourists to have a coffee experience there. This article also discusses a number of other conceptual findings regarding how Gen Z perceives the heritage precinct of Braga.